2016
DOI: 10.1002/masy.201500156
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biodegradable and Oxo‐Biodegradable Plastic Bags Samples Composition

Abstract: Plastic films used to make market bags are based on polymers such as polyethylene, polystyrene and polypropylene. These materials require a long time to degrade in the environment. Alternative technologies have been developed to reduce the degradation time and the impact on the environment caused by the conventional polymer materials, using pro-degrading additives or by the development of biodegradable polymers. In Brazil, some city's laws require the use of biodegradable material in the production of market b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Oxo-biodegradable is defined by CEN as a degradation process resulting from oxidative and cell-mediated phenomena, either simultaneously or successively. This means that the plastic undergoes degradation by oxidation until its molecular weight is low enough to be eaten by bacteria and fungi, which then recycle it back into nature by cell-mediated phenomena [31], [32].…”
Section: 32mentioning
confidence: 99%
“…Oxo-biodegradable is defined by CEN as a degradation process resulting from oxidative and cell-mediated phenomena, either simultaneously or successively. This means that the plastic undergoes degradation by oxidation until its molecular weight is low enough to be eaten by bacteria and fungi, which then recycle it back into nature by cell-mediated phenomena [31], [32].…”
Section: 32mentioning
confidence: 99%
“…The samples were heated from 30 to 500 °C at 10 °C.min -1 under argon gas flow (100 mL.min -1 ). The degree of crystallization (∆𝑋𝑋 𝑐𝑐(𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠) ) of the samples was calculated using the following eqs ( 1 ) and ( 2 ) [29][30][31].…”
Section: Film Characterizationmentioning
confidence: 99%
“…Such smaller plastic pieces represent a severe problem if animals, fish, consume them or if they are scattered over the ground. Finzi‐Quintao et al 45 were among the few researchers who studied the biodegradability of oxo‐based plastics in the landfill. It was suggested that despite utilizing oxo‐biodegradable compounds known in the literature, the composition of the bags did not permit for biodegradation in Brazilian landfill because landfills have an acid environment with no light or oxygen to permit the process of biodegradation for the studied material.…”
Section: Oxo Bio‐degradable Plasticsmentioning
confidence: 99%